Relasi Aku, Liyan, dan Budaya Dodo Orang Manggarai ( Dalam Terang Filsafat-Kritis Aku-Liyan Armada Riyanto - FERNANDES, STEFANUS (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2021)
Inside these writings, the group focuses on the theme about the relation of Me, Liyan, and Dodo Culture from Manggarai tribe (in ‘Philosophy-Critical Armada Riyanto’) based on the book titled ‘Menjadi-Mencintai and Relationalitas’. Meanwhile, the methodology which the group uses in writing is critical reading. The argument of the writing is how the philosophical view from the relation of Me, Liyan, and Dodo Culture in the Manggarai Tribe. Recently, the group often finds that humans are less aware about the meaning of the presence of Dodo culture for Me and Liyan. Armada Riyanto's philosophy has been considered as capable in explaining this view of relationality, therefore a better understanding of the presence of it can be obtained. The results of a critical reading show that the Dodo culture has contributed a lot to the development of Me and Liyan. The presence of Dodo culture makes humans unique in themselves and able to know who we and other humans are. Me and Liyan held a culture and in human pilgrimage as Me and Liyan which is experiencing a cultural presence. Humans as Me and Liyan are always in contact with culture. Armada Riyanto's philosophy defines that human beings as Me become fellow for others and see others as fellow for him and that relationship is formed by culture.